Paradoxes in Aerohydrodynamics - Yershin, Shakhbaz A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book, on the general topic of hydroaerodynamics, investigates a number of exciting applications in this field, addressing specifically issues that allow seemingly paradoxical issues to be dealt with. The first part is devoted to the study of channel flows, in particular the lateral flow of a viscous and viscous-plastic liquid in a ring channel formed by coaxial cylinders. Specifically, the problem of dissipation of mechanical energy in channel flows of highly viscous liquids is addressed and solved. Furthermore, the mechanism leading to hydrodynamic erosion in intra-field pipelines (known as "channelized effect") is identified. Subsequently, a theory for channel flows with mass transfer through porous walls is developed. In the second part, viscous liquid free flows (jets) are investigated. In particular, a dispersion law for turbulent flow is derived and the existence of dynamic invariance in wake flows of variable density is demonstrated. The third part presents new insights from both theoretical and experimental research into concentrated vortex structure formation and development. The conditions for the existence of Taylor-Goertler vortices are determined and the mechanism for their formation is described. Last but not least, the theory of vortex rings, a particularly interesting problem in hydroaerodynamics, is introduced in the last section of this book. Care has been taken, when selecting original theoretical problems of interest, to make the link with related topics in the published literature. At the same time, all experimental research described in this book is given a meaningful physical interpretation and corroborated by suitable theoretical models and computations.
Part I Channel Flows -- Viscous and Viscoelastic Flow in Annular Channels -- Hydrodynamics and Heat Transfer with Mechanical Energy Dissipation -- Round Tube Flow Crisis with Mechanical Energy -- The 'Channelized Effect' -- Channel Flows with Porous Walls -- Experimental Study of Chanel Flows with Porous Walls -- Part II Free Jet Flows -- Laminar High-Temperature Gas Jet -- Viscous Interaction Over Parallel Semi-Infinite Jets -- Turbulent Flows Dispersion -- Coaxial Jets -- Nonisothermal Turbulent Gas Jets -- Part III Concentrated Vortices -- Free Taylor-Goertler Vortices -- Theory of Vortex Rings.
Keywords: Fluid mechanics; Continuum mechanics; Engineering mathematics; Engineering -- Data processing; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Fluid Dynamics; Continuum Mechanics; Mathematical and Computational Engineering Applications; Engineering Thermodynamics, Heat and Mass Transfer